1997
DOI: 10.5144/0256-4947.1997.99
|View full text |Cite
|
Sign up to set email alerts
|

Afferent Arteriovenous Fistula in Thumb Revascularization

Abstract: A case of traumatic devascularized unviable thumb was revascularized using an afferent arteriovenous fistula. It proves again that this technique provides an alternative means of reimplantation/revascularization when no suitable artery for anastomosis is available in the devascularized/amputated part.Until now, only a few reported cases of successful reimplantation of the digits were done using afferent arteriovenous fistula.For the last decade, research studies have provided important physiological effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some authors have suggested creating an arteriovenous fistula. [5] This method is usually used when there is no suitable artery in the devascularized part. Better results are obtained when the volar veins are used for anastomosis and when there is less tension on the anastomosis between the proximal volar digital artery and the dorsal vein.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested creating an arteriovenous fistula. [5] This method is usually used when there is no suitable artery in the devascularized part. Better results are obtained when the volar veins are used for anastomosis and when there is less tension on the anastomosis between the proximal volar digital artery and the dorsal vein.…”
Section: Discussionmentioning
confidence: 99%